España lucha por su independencia. Por la paz y la solidaridad entre todos los pueblos. (Subsecretaria de Propaganda, 1936)
Workers on hilltops waving white banners. A soldier in foreground waving a white banner too Suggested translation: Spain fights for its independence. For peace and solidarity among all peoples. PO-2244